Controversies regarding the Change of the Legal Framework during the Trial of the Offense Stipulated by art. 132 of the Law no. 78/2000 referring to art. 297 para. 1 Criminal Code - Gradinaru, Sandra (Acta Universitatis Danubius. Juridica, 2024)
The institution of changing the legal framework of the crime is a right of the court that aims to restore the identity between the act and its classification in law in case the identification of the rule of law was made wrong, or the data in which the deed was committed were not correctly retained. This right of the court must be accompanied by procedural guarantees established in favor of the defendant, so that his right to defense is respected. We appreciate that a request to change the legal framework formulated by the prosecution at the end of the court investigation, after administering all the evidence that would make the situation of the defendant difficult and that does not result from a change in the factual situation retained in the indictment, the, but based solely on the error of the case prosecutor in retaining an aggravating circumstance can not be received by the court. We also appreciate that the incidence of a case of termination of the trial must be analyzed by the court with priority before any other request. Thus, the institution of changing the legal framework cannot be used to supplement the subject of criminal action and to cover the effects of fulfilling the limitation period of criminal liability